Obstetric shock. Shock anesthetic. - Gayoso Bacigalupo, Alejandro (2015)
It is incontrovertible that the different actors, and the different techniques used in obstetric anesthesia are capable of producing shock. But it is equally true that the dreaded complication usually stems from one of the following circumstances: poor anesthetic choice, poor use of techniques, mismanagement of complications or presentation of special situations iatrogenic order.